Comparison of visual analysis, non-overlap methods, and effect sizes in the evaluation of parent implemented functional assessment based interventions. (February 2019) - Barton, Erin E.; Meadan, Hedda; Fettig, Angel
Highlights: Authors frequently used mean/median/average to describe their results. Overall the magnitude ratings did not correlate with TAU or NAP. There is a need for transparent and consistent visual analysis procedures. Visual analysis is currently the only way to identify functional relations. Abstract: We used an existing body of research (i.e., parent implemented functional-assessment based interventions) to examine visual analysis features and processes and evaluate the reliability of two frequently used non-overlap indices (NAP & Tau-U) and a novel effect size index—the between-case standardized mean difference (BC-SMD). Results indicated that visual analysis terms and procedures were inconsistently used across studies. Further, there was limited agreement between the non-overlap indices and independent visual analysis. Results regarding the BC-SMD were inconclusive given only 5 of the 15 studies were eligible for analyses for different dependent variables. Our results suggest that visual analysis standards are needed by which single case researchers analyze and report their results. Further, additional research is needed refining SCR effect sizes, which can be used to describe the magnitude of change within and across SCR studies with functional relations.